Effect of Non-Uniform Soiling on Solar Panel Output and Revenue Analyzed Through a Controlled Experiment by Using a Designed I-V Scanner - Islam, Mohammad Didarul; Islam, Md Aminul; Khan, M Ryyan (MIST International Journal of Science and Technology, 2022)
Non-uniform soiling drastically decreases the power generation of PV panels. Different events are responsible for the non-uniform soiling on PV panels for example bird droppings, sand storms, or snowfall. In this study, we have achieved multiple-goals for analyzing the effect of non-uniform soiling on a PV module output. We also analyzed the revenue losses due to the non-uniform soiling in a PV power plant. Firstly, for observing the effect of non-uniform soiling an I-V scanner has been designed. Secondly, the designed I-V scanner has been used to observe the changes in the I-V characteristics curve of PV panels due to non-uniform soiling and shading conditions. In this study, we have conducted various controlled experiments by providing different shading conditions on the PV panel and observing the I-V curve changes. A correlation has been done with the various shadowing conditions like the bottom edge soiling condition of PV panels or bird-dropping. In a PV power plant, nonuniform soiling may occur at the edge of PV panels after cleaning intervention. Considering these scenarios, we have done an economic analysis for determining the effect of non-uniform soiling on the revenue of PV power plants. Finally, the relations between the cleaning cycle, performance loss factor, and solar cell area coverage with respect to revenue have been also discussed in this article. MIJST, Vol. 10, December 2022: 21-28 DOI: https://doi.org/10.47981/j.mijst.10(03)2022.346(21-28)